REGIONALIZATION MODELS IN MUNICIPAL PLANNING, LIMITS, INTER-CAPITAL COMPARISONS AND PROPOSED CRITERIA FOR MACEIÓ - Nicácio, Jailton Pereira (Seven Editora, 2025)
The study critically examines the regionalization models adopted in Brazilian municipal planning, with a specific focus on the case of Maceió. It assumes that regionalization is a structuring element of territorial state capacity and of the effectiveness of planning instruments such as the Multi-Year Plan, the Budget Guidelines Law and the Annual Budget Law. This qualitative research employs document analysis, literature review and inter-capital comparison to assess the technical, institutional and functional criteria guiding territorial delimitation in Brazilian capitals. Maceió’s model, based on neighborhood subdivision and consolidated since 1988, is contrasted with benchmark experiences and with capitals of similar characteristics. The analysis adopts as methodological reference the Regionalization Model for State Planning of Alagoas, grounded on the principles of polarization and socioeconomic flows. The findings show that Maceió’s current regionalization lacks technical criteria, which compromises diagnostics, prioritization and the territorial allocation of public expenditure. The study concludes that it is necessary to advance toward a standardized municipal regionalization model, articulated with indicators, data and participatory processes, capable of supporting more efficient planning oriented toward territorial inequalities.DOI: https://doi.org/10.56238/sevened2025.036-093